Financial Performance Analyzing Factors of Banking Industry: Challenges and Opportunities in the Indian Banking Industry (Journal of Advances and Scholarly Researches in Allied Education, 2020)
In a country's economic growth, banks play an essential role. They are the lifeblood of contemporary business and control most of the supply of money. A bank is a financial broker that receives deposits and transfers them to lending. It plays an important role in the marketing and promotion of new types of deposits. The key areas for monitoring the performance of a bank are operational efficiency, service quality and management efficiency. A bank's financial performance is assessed in terms of profitability, service, customer happiness and other important elements as the bank's success. The profitability of a bank refers to the efficacy of a bank's entire resources to optimize their net earnings, and is thus a measure of the use of assets and the effectiveness of the management. There are a lot of severe problems facing the Indian financial system at now.